1990
DOI: 10.1111/j.1151-2916.1990.tb05209.x
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of a Particulate‐Reinforced Ceramic‐Matrix Composite by Thermal Residual Stress

Abstract: The micromechanics involved in increased crack growth resistance, KR, due to the addition of TiBz particulate in a SIC matrix was analyzed both experimentally and theoretically. The fractography evidence, in which, the advancing crack was attracted to adjacent particulates, was attributed to the tensile region surrounding a particulate. Countering this effect is the compressive thermal residual stress, which results in the toughening of the composite, in the matrix. This thermal residual stress field in a part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
204
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(238 citation statements)
references
References 26 publications
2
204
1
1
Order By: Relevance
“…Since the pioneering work of Niihara (1991) (Golla and Basu, 2014;Yamamoto et al, 2008;He et al, 2009;Wang and Steven, 1989;Nieto, Lahiri, and Agarwal, 2012;Liu et al, 2012;Chae et al, 2006;Choa et al, 1998;Gao et al, 1999aGao et al, , 1999bTaya et al, 1990). One of the motivations for interest in SiC-reinforced composites is the toughening mechanism associated with the composites, referred to as residual stress toughening.…”
Section: Spark Plasma Sintering (Sps) -An Advanced Sintering Techniquementioning
confidence: 99%
“…Since the pioneering work of Niihara (1991) (Golla and Basu, 2014;Yamamoto et al, 2008;He et al, 2009;Wang and Steven, 1989;Nieto, Lahiri, and Agarwal, 2012;Liu et al, 2012;Chae et al, 2006;Choa et al, 1998;Gao et al, 1999aGao et al, , 1999bTaya et al, 1990). One of the motivations for interest in SiC-reinforced composites is the toughening mechanism associated with the composites, referred to as residual stress toughening.…”
Section: Spark Plasma Sintering (Sps) -An Advanced Sintering Techniquementioning
confidence: 99%
“…The residual stresses were estimated with the modified Eshelby model proposed by Taya et al [20]. In the model, the isotropic average stress fields in the Al 2 O 3 matrix and Y-TZP particulate can be theoretically estimated from the volume fraction, elastic modulus, Poisson's ratio and thermal expansion coefficients of the phases.…”
Section: Fig 2 Representative Tof Neutron Diffraction Pattern Analymentioning
confidence: 99%
“…(BASU, VLEUGELS, 2001). The residual stress in zirconia matrix was calculated according to the model proposed by Taya (TAYA et al, 1990) and confirmed by Shi (SHI et al, 2000). In the calculations we used the modulus of elasticity (E) from 90GPa to 190GPa for the Bioglass and ZrO 2 .…”
Section: Residual Stressesmentioning
confidence: 99%
“…The calculation of the average thermal residual stress generated during cooling of the sintered samples was based on the consideration that there is homogeneous distribution of second phase in ceramic matrix ZrO 2 , and is directly related to the difference in thermal expansion coefficients between the phases in the ZrO 2 matrix and intergranular glassy phase, composed of Bioglass (TAYA et al, 1990;SHI et al, 1998). Was not taken into account the hypothesis of partial crystallization of the glass or the temperature range where there is softening of the glass present.…”
Section: Residual Stressesmentioning
confidence: 99%